Learning Society dalam Membentuk Civil Society pada Siswa SMP Asa Cendekia Sedati Sidoarjo - Putri, Sakia Amanda Deviana; Masnawati, Eli (TSAQOFAH, 2024)
Learning Society is an alternative discourse in the field of education that focuses on how education can be accessed anytime and anywhere, regardless of space and time. Every activity undertaken is always understood as a learning process. Therefore, schools are everywhere, not just formal institutions. Civil society today is a discourse that has gone through a lengthy process. It emerged as part of modernization and democratization, and at that time was more commonly known as civil society. Civil Society is a uniquely organized social environment. We uphold values of independence, self-reliance, personal responsibility, democracy, and good morals. The research method uses a qualitative approach with a descriptive approach, and data collection techniques are carried out through interviews, observations, and documentation. The results of this study are the civil society formed at SMP Asa Cendekia Sedati Sidoarjo and the learning society in shaping the civil society of students.